Language, power, and gender in transnational education: A feminist critical discourse analysis of women’s representation in We Need New Names - Mahmood, Hassan; Nusrat, Aasia; Shlowiy, Ahmed Al; Khoso, Abdul Khalique (Journal of International Students, 2026)
In this paper, we use feminist critical discourse analysis (FCDA) to study the linguistic aspects that shape and frame gendered power and relations in We Need New Names by NoViolet Bulawayo. Through qualitative analysis of dialogues, narrative structures, and silences, we highlight how patriarchal norms are reinforced and challenged. The findings reveal four categories derived from the analysis: silence as resistance; silence as socialization; language marginalization in diaspora settings; and the inversion of colonial-patriarchal discourse. The findings suggest that silence in the novel can function simultaneously as a patriarchal disciplinary measure and a resistant counter discourse, enabling women to exercise their agency. The results also suggest how hybrid and diminished linguistic presence in the diaspora setting is symptomatic of the intersections of gender and cultural hegemony.